Influences of heat input, welding sequence and external restraint on twisting distortion in an asymmetrical curved stiffened panel. (January 2018) - Liang, Wei; Deng, Dean
Highlights: A new computational approach based on inherent strain theory and interface element method was employed to estimate the total welding-induced deformation for large welded structures. The features of welding deformation in an asymmetrical curved stiffened panel was studied. Simulation results show that angular distortion is the main reason resulting in the twisting distortion of the curved stiffened panel. Heat input, welding sequence and external restraint can significantly affect the final deformation of the curved stiffened panel. Abstract: Welding distortion not only degrades the fabrication accuracy of ship hull blocks but also decreases the productivity due to correction works. The accurate prediction of welding-induced distortion will help control the dimension accuracy. In this study, a computational approach based on inherent strain theory and interface element method was employed to efficiently and precisely estimate welding-induced deformation for large welded structures generated during assembly process. In the proposed approach, the local shrinkage due to heat input were considered by inherent strain components. On the other hand, the gap as well misalignment between the two parts to be joined, and the change of stiffness during assembly process were taken into account by interface elements. Meanwhile, the geometrical nonlinearity was included in the developed computational approach. In the current study, the features of welding deformation in an asymmetrical curved stiffened panel were numerically investigated by mean of the new computational approach. In addition, the influences of heat input, welding sequence and external restraint on the twisting distortion of the curved stiffened panel were further studied.